Knowledge, Behavior and Motivation of Students About Vaginal Hygiene and Prevention of Pathological Leucorrhoea at Female Islamic Boarding School - Panghiyangan, Roselina; Fakhriadi, Rudi (Lambung Mangkurat University, 2024)
Vaginal discharge is a symptom that is very often experienced by most women. Vaginal discharge is divided into two types, namely physiological and pathological discharge. Pathological vaginal discharge can be said to be abnormal vaginal discharge caused by infection or inflammation. The purpose of this study was to see the effectiveness of counseling on increasing knowledge, behavior, and motivation of female students towards vaginal hygiene and prevention of pathological leucorrhoe at boarding schools. This research method is quasi experiment with pre-test dan post-test group design. The population in this study were Aliyah students in grade 1, grade 2 and grade 3 totaling 130 students. The sample used in this study was proportional stratified random sampling, namely 64 female students. The results of the Wilcoxon test showed a p-value of 0.0001 (p < 0.05) on all variables, which means that there are differences in knowledge, behavior and motivation between before and after counseling. The conclusion of this study is that counseling is effective in increasing the knowledge, behavior and motivation of female boarding school students.